A Philosophical Perspective on The Islamic View of Business in South Africa - Mohammed Ntshangase (CV. FOUNDAE, 2025)
This study explores the philosophical foundations of the Islamic view of business among Muslim entrepreneurs operating in rural South African communities. The research addresses the problem of understanding why Muslim business owners prioritize trust, hope, and humanitarian service above mere profit-making, despite operating in socio-economically disadvantaged environments. Using a qualitative approach supported by semi-structured interviews with ten purposively selected participants five Muslim shop owners and five community members the study applies thematic analysis guided by critical social theory. The analysis reveals that Islamic financial philosophy shapes a business culture rooted in care, kindness, fairness, and community upliftment. Muslim entrepreneurs perceive business not only as an economic activity but also as a religious duty grounded in serving humanity, maintaining ethical conduct, and seeking divine pleasure. Findings show that these philosophical commitments strengthen social trust, promote communal harmony, and help alleviate local poverty. The study concludes that Islamic financial philosophy offers a transformative alternative to profit-driven business models and has the potential to support sustainable community development. Limitations include restricted sample size and reliance on interview data, suggesting that future research should incorporate broader case studies and comparative analyses across regions.